Conventional Radiotherapy and Stereotactic Radiosurgery in the Management of Metastatic Spine Disease - Hao-ran Zhang MD; Ji-kai Li MD; Xiong-gang Yang MD; Rui-qi Qiao MD; Yong-Cheng Hu MD, PhD (Technology in Cancer Research & Treatment, 2020)
Spinal metastases are a common manifestation of malignant tumors that can cause severe pain, spinal cord compression, pathological fractures, and hypercalcemia, and these clinical manifestations will ultimately reduce the health-related quality of life and even shorten life expectancy in patient with cancer. Effective management of spinal bone metastases requires multidisciplinary collaboration, including radiologists, surgeons, radiation oncologists, medical oncologists, and pain specialists. In the past few decades, conventional radiotherapy has been the most common form of radiotherapy, which can achieve favorable local control and pain relief; however, it lacks precise methods of delivering radiation and thus cannot provide sufficient tumoricidal dose. The advent of stereotactic radiosurgery has changed this situation by using highly focused radiation beams guided by 3-dimensional imaging to deliver a high biologic equivalent dose to the target region, and the spinal cord can be identified and excluded from the target volume to reduce the risk of radiation-induced myelopathy. Separation surgery can provide a 2- to 3-mm safe separation of tumor and spinal cord to avoid radiation-induced damage to the spinal cord. Targets for separation surgery include decompression of metastatic epidural spinal cord compression and spinal stabilization without partial or en bloc tumor resection. Combined with conventional radiotherapy, stereotactic radiosurgery can provide better local tumor control and pain relief. Several scoring systems have been developed to estimate the life expectancy of patients with spinal metastases treated with radiotherapy. Thorough understanding of radiotherapy-related knowledge including the dose-fractionation schedule, separation surgery, efficacy and safety, scoring systems, and feasibility of combination with other treatment methods is critical to providing optimal patient care.